Four new earthworm species of the genus Amynthas (Oligochaeta: Megascolecidae) from Kinmen, Taiwan - Shen, Huei-Ping; Chang, Chih-Han; Li, Chi-Lun; Chih, Wen-Jay; Chen, Jiun-Hong (Zootaxa, 2013)
Four new species of terrestrial earthworms belonging to the genus Amynthas were collected on the islands of Kinmen and Lieyu, Taiwan from March to November, 2008. They are Amynthas kinmenensis sp. nov., Amynthas wuhumontis sp. nov., Amynthas wujhouensis sp. nov., and Amynthas taiwumontis sp. nov. Amynthas kinmenensis sp. nov. is quadrithecal and is the most abundant earthworm widely distributed on the main island of Kinmen. It has numerous small genital papillae and is closely related to Amynthas polyglandularis (Tsai, 1964) from northern Taiwan. Amynthas wuhumontis sp. nov. is sexthecal and is distributed only in areas around Mt. Wuhu and Mt. Taiwu in east Kinmen. It has male pores each surrounded by three genital papillae: one anterior, one posterior and one medial. Amynthas wujhouensis sp. nov. and Amynthas taiwumontis sp. nov. are octothecal. The former has a sporadic distribution in Kinmen while the latter was only found in areas around Mt. Taiwu. Amynthas wujhouensis sp. nov. has a pair of large genital papillae closely adjacent to the crescent or semicircular shaped male porophores in XVIII. Amynthas taiwumontis sp. nov. has simple male pore structure and no genital papillae or genital markings. DNA barcodes (the 5’ end sequences of the mitochondrial cytochrome c oxidase subunit 1 gene) from type specimens and other materials of the first three species are also reported.